Efektifitas Peran Psikolinguistik terhadap Kemampuan Bahasa Arab Santri di MA Putra Al-Ishlahuddiny Kediri - Zarkani, Moh. (Lembaga Bale Literasi, 2026)
Arabic language learning in madrasahs still faces serious challenges, particularly the gap between understanding grammatical theory and practical language skills. Students at MA Putra Al-Ishlahuddiny Kediri exhibit various psycholinguistic barriers, including phonological difficulties, mother tongue interference, morphosyntactic constraints, anxiety, limited vocabulary, and pragmatic errors. This situation underscores the urgency of adopting a psycholinguistic analysis approach as a more relevant alternative to traditional rote memorization methods. This study aims to address how psycholinguistic factors influence students' Arabic language abilities and what strategies can support more effective language mastery. The research employs a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted inductively through stages of reduction, presentation, and conclusion drawing. The findings indicate that students' Arabic language ability is influenced by a combination of cognitive factors (memory, phonological processing), affective factors (anxiety), and social factors (code-switching practices, cultural identity). Students struggle to distinguish similar phonemes, frequently transfer syntactic structures from Indonesian, and demonstrate limited vocabulary and listening comprehension. Code-switching was identified as both a communicative strategy and an expression of identity. These findings enrich the psycholinguistics literature by providing empirical evidence from the Indonesian pesantren/madrasah context, which has been underrepresented in global research. In conclusion, psycholinguistic factors significantly impact Arabic language acquisition. The implications of this study emphasize the need to integrate psycholinguistic strategies into the madrasah curriculum, such as structured phonological exercises, repeated vocabulary retrieval, anxiety management, and social support in the classroom. Further research is recommended using quasi-experimental and longitudinal intervention designs to examine the causal and long-term effectiveness of psycholinguistic strategies.